2017
DOI: 10.2147/lctt.s142880
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Glasgow prognostic score and prognostic nutritional index predict overall survival of patients with advanced small cell lung cancer

Abstract: BackgroundVarious biomarkers have been shown to predict prognosis in various types of cancers. However, these biomarkers have not been studied in advanced small cell lung cancer (SCLC). The modified Glasgow prognostic score (mGPS) is based on serum albumin level and C-reactive protein (CRP). The prognostic nutritional index (PNI) is a combination of serum albumin level and absolute lymphocyte count. This study aimed to evaluate the prognostic value of mGPS and PNI in SCLC.MethodsWe retrospectively reviewed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 14 publications
4
53
0
Order By: Relevance
“…A recent study also demonstrated that pretreatment mGPS and PNI are independent predictors of OS in patients with advanced SCLC [14]. In line with these studies, pretherapeutic elevated serum albumin, CRP, and LDH, decreased sodium, as well as a high mGPS and high PI were also significantly associated with reduced PFS in our study cohort.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A recent study also demonstrated that pretreatment mGPS and PNI are independent predictors of OS in patients with advanced SCLC [14]. In line with these studies, pretherapeutic elevated serum albumin, CRP, and LDH, decreased sodium, as well as a high mGPS and high PI were also significantly associated with reduced PFS in our study cohort.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have already identified pretherapeutic prognostic markers and scores to predict outcome in SCLC patients [7,8,9,10,11,12,13,14]. A recent study also demonstrated that pretreatment mGPS and PNI are independent predictors of OS in patients with advanced SCLC [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembrolizumab was approved as the first-line regimen for a specific population of NSCLC by Japanese medical insurance in December 2016, and has been available in our hospital since March 2017. The methods, classifications and definitions of clinical profiles, creatinine clearance (Ccr), NLR, LMR, mGPS, response rate (RR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS) followed those of our previous studies [ 15 , 16 ]. The data cutoff was December 31, 2017.…”
Section: Methodsmentioning
confidence: 99%
“…In various types of cancers, including advanced NSCLC, higher NLR [ 8 - 10 ], lower LMR [ 11 , 12 ] and Glasgow prognostic score (GPS) class 2 [ 13 , 14 ] are independent prognostic markers for shorter survival. Our previous studies also demonstrated that NLR for NSCLC with active EGFR mutation [ 15 ], LMR and mGPS for adenocarcinoma without any driver mutation, and mGPS for small cell lung carcinoma [ 16 ] were significant prognostic factors. However, it is not clear that these three prognostic markers are also useful for patients with advanced SCC.…”
Section: Introductionmentioning
confidence: 93%